Damage Classification on Bridges using Backpropagation Neural Network - Victoria Ivy Tansil; Novita Hanafiah; Alexander Agung Santoso Gunawan; Dewi Suryani (Engineering, MAthematics and Computer Science (EMACS) Journal, 2021)
Bridge structures can be damaged due to various factors such as pressure, vibration, temperature, etc. This study aims to detect damaged on bridges early so that accidents that can occur due to the damaged-on bridge can be avoided. The research method is divided into designing a model, building the model, and evaluating the model. The result of this research is a program that can classify healthy or damaged bridges using vibration data of tested points on bridges.